2010
DOI: 10.1021/jm100078r
|View full text |Cite
|
Sign up to set email alerts
|

Complexity in Influenza Virus Targeted Drug Design: Interaction with Human Sialidases

Abstract: With the global spread of the pandemic H1N1 and the ongoing pandemic potential of the H5N1 subtype, the influenza virus represents one of the most alarming viruses spreading worldwide. The influenza virus sialidase is an effective drug target, and a number of inhibitors are clinically effective against the virus (zanamivir, oseltamivir, peramivir). Here we report structural and biochemical studies of the human cytosolic sialidase Neu2 with influenza virus sialidase-targeting drugs and related compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 24 publications
4
71
0
Order By: Relevance
“…Assays were conducted using methods previously reported from our department. 36,37 The data for inhibition, obtained for all the 4α-amino substituted derivatives, compared with those obtained for the parent a Each value represents the mean ± standard deviation of two or three independent experiments carried out in triplicate.…”
Section: Resultsmentioning
confidence: 99%
“…Assays were conducted using methods previously reported from our department. 36,37 The data for inhibition, obtained for all the 4α-amino substituted derivatives, compared with those obtained for the parent a Each value represents the mean ± standard deviation of two or three independent experiments carried out in triplicate.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in orientation of the guanidino group in 8 may contribute to the retained activity of this inhibitor against influenza viruses with a Glu119 mutation that have reduced susceptibility to zanamivir [162]. In binding with the human sialidase Neu2, the cyclopentane derivative 8 appeared to be stabilized mostly by the carbox ylic acid group, with fewer overall hydrogen bonds than were seen for zanamivir, providing a rationale for the weaker inhibitory activity of 8 against Neu2 compared to zanamivir [125].…”
Section: A Sialidase Inhibitor Based On a Cyclopentane Scaffold: The mentioning
confidence: 99%
“…Against Neu2 and Neu3, this inhibition is slightly stronger than that of Neu5Ac2en 14. For Neu2 this has been attributed, based on X-ray structures of the Neu2:5 and Neu2:14 complexes, to the formation of additional hydrogen bonds to the C4 guanidino group of 5 [125]. The IC 50 (6.8 μM) for 5 against the plasma membrane Neu3 is substantially ( 1000-fold) greater than that observed for 5 against influenza virus sialidases (IC 50 ∼ 2 nM) [124].…”
Section: Selectivity For Influenza Virus Sialidase Over Human Sialidasesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that although recombinant human sialidases are not affected by oseltamivir, peramivir and zanamivir may inhibit these enzymes at high concentrations. 6 To screen for a possible underlying mild neuraminidase deficiency (sialidosis) in our patient, we assayed urinary oligosaccharide excretion, which was normal.…”
Section: Go To Sectionmentioning
confidence: 99%